Analisis Sistem Penanggulangan Gawat Darurat Terpadu Melalui Implementasi Jember Safety Center Di Kabupaten Jember - Desy Iswari Amalia; Isa Ma’rufi; Dewi Rokhmah (Pascasarjana Universitas Jember, 2020)
Some incidence of emergency in Jember District tends to increase every year. The Jember Safety Center (JSC) is an alternative solution to problems carried out by the Jember District in dealing with the high number of emergency cases in Jember District. Based on the results of the preliminary survey, researchers find several aspects, tasks, and functions of the JSC that have problems in its implementation. These problems indicate the need for more in-depth research related to the input and process aspects of the implementation of the JSC in Jember District. This study aims to analyze an integrated emergency response system through the implementation of the Jember Safety Center in Jember District. This type of research is qualitative research with a case study approach. The data analysis technique used the Miles & Huberman analysis model. They are data collection, data reduction, data presentation, and conclusions. This research is taken place at the location of the JSC call center, the Jember District Health Office, the Public Health Center in Jember District, the JSC user home, and the Soebandi Jember Hospital. The results of the study show that the need for human resources in organizing the Public Safety Center is guided by the Minister of Health Regulation Number 19 of 2016. However, the quality of human resources needs to be improved. The current budget given by the government is still focused on the physical budget and JSC equipment. Information and emergency calls from the community are still lacking, this is due to inadequate socialization, and not all services via the village ambulance are recorded through the JSC Call Center. It is necessary to improve the service management of JSC as the center for the Integrated Emergency Management System (SPGDT) in Jember District. Improvements are made by taking into account the input aspects consisting of Men, Money, Materials, Machines, and Methods in the Implementation of the Jember Safety Center in Jember District to improve services JSC to the community in Jember District Keywords: Jember Safety Center, Emergency, AKI and AKB